The Estimation of Ketapang (Terminalia catappa Linn.) Tree’s Transpiration - Sri Wahyuni; Mar’atul Afidah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Ketapang (Terminalia catappa Linn.) is a coastal tree with a fairly wide distribution area. The utilization of ketapang has not been carried out optimally. Ketapang is only used as a shade tree. For this reason, it is necessary to do a lot of research in exploring the various benefits of ketapang. One of the basic studies to determine the potential of ketapang is to estimate the transpiration of ketapang tree. The results of this study can be used as a basis for the use of ketapang as a tree that has the potential for sustainable environmental management. The purpose of this study was to determine the estimated transpiration of ketapang tree. This research is a qualitative survey research. This research uses purposive sampling technique. The sample in this study is ketapang tree that grows in the FKIP environment of Lancang Kuning University. The research data were analyzed by using the formula for the estimation of the amount of water from transpiration in one tree. The results showed that the estimated transpiration in ketapang tree averaged 17,330 ml within 24 hours. The ketapang tree has an important role in ecological functions, especially in maintaining the water cycle. It is necessary to conduct similar research on other tree species in order to obtain tree species that have the potential to be developed as trees with high ecological functions.